Bajo los vestigios de un cuerpo: cultura, discurso y acontecimiento - Vilela, Eugénia (CALLE14: revista de investigación en el campo del arte, 2011)
In contemporary time, at the same time that is given an uncontrolled cultural and social multiplication of the figures of the body, its sense escapes indefinitely. The question “what’s the body?” constitutes an archaic and urgent question. The fascination and obsession for the representation of the body carried out from art and childhood, make us wonder for the reason of the origin of the preference for the body in representation. In these representations —in painting, photography, sculpture, movies, dance— the way in which a body is perceived it’s important, as well as what it is searched when looking at it, because a gaze doesn’t settle in a body like over a thing. This gaze looks for an underground pulsation. To explore a living body is to explore signs that constitute an expressive load. The human body is expressive: it shows something that is not seen, and for that reason it’s a field of signs. The expression comes, justly, from that you don’t see. And, unconsciously, what hides from the gaze is hidden inside the body: under the skin.